THE SOCIALIZING EFFECT OF ACTIVITY IN THE CENTER OF FOOD PREPARATION ACCORDING TO THE «STEP BY STEP» PROGRAM - Vatamaniuk, Halyna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article highlights some aspects of preschooler socialization, the conceptual principles of the «Step by Step» comprehensive development program of a child from birth to 12 years old. The pedagogical potential of classes in the cooking center regarding the social development of preschoolers is described.